PENGEMBANGAN TANAMAN KAKTUS DAN SUKULEN SEBAGAI MINI GARDEN UNTUK PENINGKATAN IPTEK DAN KEWIRAUSAHAAN SANTRI PONDOK PESANTREN NURUL ISLAM JEMBER - Denna Eriani Munandar; Muhammad Nur Khozin; Widya Kristiyanti Putri (Jurnal Abdi Insani, 2022)
Cactus and succulents have promising potential as a mini garden in terms of beautification scenery function and economy. This program's dedication to partner of the programme is students of Pondok Pesantren Nurul Isman (PP NURIS) Jember, a group of Masdrasah Sain (M-Sain). The partner problem was the students have not known yet about cactus and succulent benefits, agriculture, nursing, and entrepreneurship. One of them is the creation of a mini garden that has high economic value. The program's dedications to partner of the programme objectives were to increase student's knowledge about the benefits, propagation, and nursery of cactus and succulents; and to motivate entrepreneurial spirit. The methods that were used subsequently: were problem identification and solutions, giving presentations, propagation practices, nursery, and technique of cactus and mini garden. As a result, students actively got motivated and participated in every phase from giving presentations to making the mini garden. In conclusion, there was increasing in student knowledge about benefits, propagation, the nursery of cactus and succulents, and mini gardens production.